Jimmy Du's essential Chinese : Jimmy Du's natural language works - Du, Zhengming (Cambridge Scholars Publishing, 2016)
As the first self-teaching course in Jimmy Du's Natural Language Works, Jimmy Du's Essential Chinese is an audio-companion book specially designed to help you master Mandarin Chinese in the shortest time possible. The promise is that you will simply "pick it up" if you just spend a little time following this course while relaxing at home, taking a walk, commuting to work or travelling. You don't have to sit in a classroom, consult the dictionary, study grammar or do any written exercises. This least-effort principle is based on the understanding that we human beings all have an innate aptitude